The Effectiveness of Using Talking Chips Strategy for Students’ SpeakingAbility of The VIII B Grade At MTs NU Gombengsari in The Academic Year 2017/2018 - Sofia Amalia; Yuli Sugianto; Nur Hasibin (LUNAR, 2019)
There are several skills to master English as international language must be taught in teaching learning process that is listening, speaking, reading and writing. This research explores the experimental research of effectiveness in using talking chips strategy for students’ speaking ability of Eighth B grade at MTs NU Gombengsari in the 2017/2018 academic year. The primary data were taken from pre test and the secondary data were taken from post test. The numbers of respondents are 34 students in the population that uses purposive sampling. The purpose of this research was intended to know the effectiveness of talking chips strategy for students’ speaking ability and to find out the significant different of students speaking ability in vocabulary, pronounciation and independence. In this research, the researcher used the pre test and post test as data collecting method and t-test formula as data analysis. There are 1,65% of the effectiveness of talking chips startegy that had been applied. The degree of value of this research is stated in 32. The result of talking chips strategy is able to increase the achievement of speaking ability. Learning description of speaking ability using talking chips strategy is easier for the students to explore their ideas.